Copper-catalyzed intramolecular N-arylation of quinazolinones: facile convergent approach to (-)-circumdatins H and J - Kshirsagar, Umesh A.; N. P. Argade (Organic Letters, 2010)
A copper-catalyzed intramolecular N-arylation of a quinazolinone nucleus that furnished the central benzodiazepine core unit has been demonstrated to accomplish an efficient convergent total synthesis of (-)-circumdatins H and J.